Clinical and Bacteriological Study of Chronic Suppurative Otitis Media by Anaerobic Culture Methods in a Teaching Hospital - Kumar, Jagdish; Hima, Bindu P (Nepalese Journal of ENT Head and Neck Surgery, 2014)
DOI: http://dx.doi.org/10.3126/njenthns.v3i2.10155 Nepalese Journal of Head and Neck Surgery Vol.3(2) 2012: 12-14